UNDERSTANDING THE TRANSMISSION PATTERNS OF COVID-19 - Mohammed Saad S Aldosari, Hamad Ahmad Al Saigh, Hamad Ibrahim Al Ghareeb, Saad Awad Almarzzouk, Naif Saeed Al Shahrani, Binshalhob, Zaid Abdulaziz A, Nasser Faleh Alghatani, Ibrahim N M Aldhuwailea,; Bandar Saleh Rashed Al Khara, Abduaziz Rashed Zaid Bin Gannam, Ali Abdulaziz Almuslim (Chelonian Research Foundation, 2022)
The study of the occurrence and distribution of COVID-19 highlights the significant impact of age and the presence of other medical conditions on the severity of the illness and the likelihood of death. Older persons, especially those aged 70 and beyond, are at a much elevated risk of experiencing serious disease and mortality. Coexisting medical conditions including hypertension, diabetes mellitus, and cardiovascular illnesses worsen the results of COVID-19, emphasizing the need of customized preventative measures and integrated healthcare treatments. The variability in the virus's ability to propagate, as shown by calculations of the reproductive number (R0), highlights the ever-changing nature of its transmission and the need for flexible public health interventions. Discrepancies in medical facilities and socioeconomic variables throughout the globe lead to different results in various nations and areas. This highlights the need of fair access to resources and well-coordinated international collaboration. Gaining a comprehensive understanding of the epidemiological characteristics of COVID-19 is essential for developing policies and actions based on solid research, with the aim of reducing its effect and eventually ending the pandemic. Key Words: Transmission, COVID-19, Epidemiology, reproductive number, Infection, medical facilities.